Comparison of a 32-channel head coil and a 2-channel surface coil for MR imaging of the temporomandibular joint at 3.0 T - Manoliu, Andrei (Dentomaxillofac Radiol, 2016)
OBJECTIVE: To quantitatively and qualitatively compare MRI of the temporomandibular joint (TMJ) using a standard TMJ surface coil and a head coil at 3.0 T. METHODS: 22 asymptomatic volunteers were MR imaged using a 2-channel surface coil (standard TMJ coil) and a 32-channel head coil at 3.0 T (Philips Ingenia; Philips Healthcare, Netherlands). Imaging protocol consisted of an oblique sagittal proton density weighted turbo spin echo sequence (repetition time/echo time, 2700/26 ms). For quantitative assessment, a spherical phantom was imaged using the same sequence including a noise scan and a B1+ scan. Signal-to-noise ratio (SNR) maps and B1+ maps were calculated on a voxelwise basis. For qualitative evaluation, all volunteers underwent MRI of both TMJs with the jaw in the closed position. Two independent blinded readers assessed accuracy of TMJ anatomical representation and overall image quality on a 5-point scale. Quantitative and qualitative measurements were compared between coils using t-tests and Wilcoxon signed-rank test, respectively. RESULTS: Quantitative analysis showed similar B1+ and significantly higher SNR for the head coil than the TMJ surface coil. Qualitative analysis showed significantly better visibility and delineation of clinically relevant anatomical structures of the TMJ, including the articular disc, bilaminar zone and lateral pterygoid muscle. Furthermore, better overall image quality was observed for the head coil than for the TMJ surface coil. CONCLUSIONS: A 32-channel head coil is preferable to a standard 2-channel TMJ surface coil when imaging the TMJ at 3.0 T, because it yields higher SNR, thus increasing accuracy of the anatomical representation of the TMJ.